Analysis of Available Blend Refrigerants for Medium-high Temperature Cascade Heat Pump - Wu Xi; Xu Shiming; Liu Jiawei; Dai Xiaojun; Zhao Wenzhong (Zhileng xuebao)
Five pairs of binary blend refrigerants with small temperature glides are proposed to be used in medium-high temperature cascade heat pumps according to the results of theoretical comparative studies, including thermophysical properties, cycle performance, environmental impact, and flammability of several potential working fluids under the refrigerants developing criterion. While R161/R1234yf and R161/R290 are found to be suitable to the sub-system of the low-temperature heating cycle, R152a/RE170, R152a/R1243zf, and R245fa/R1234zeZ are practical in the high-temperature heating cycle sub-system. Compared to the common cascade heat pump running with refrigerants R22+R134a, it is discovered that blend refrigerants that consist of R161/R1234yf+R152a/RE170 or R161/R290+R152a/RE170 possess optimal comprehensive performances. These blend refrigerants have the highest coefficient of performance （COP） of 1.58, under hypothetical working conditions for producing hot water at 80 °C. Special attention should be paid to their flammability. When using R245fa/R1234zeZ in the sub-system of high-temperature heating cycle, both the high pressure and flammability risk can be reduced significantly. In addition, the condensing temperature of system can be as high as 120 °C (about 2.1 MPa in pressure), and it would be better if using the compressor with a large working volume.